Extradition of war criminals under the rules of international humanitarian law - Laouar, Hacen Hamza (Journal of Human Sciences, 2021)
The extradition of persons accused of war crimes, and crimes against humanity and genocide during armed conflicts is among the most important topics on the international scene Especially that there are many fugitive war criminals who have not yet been tried and punished because of their presence either  in their own countries as protected persons or externally as refugees; which raises the issue of fair trial in accordance with the international rules and principles in force or, on the opposite, national laws may provide them with protection because they may not allow the extradition of nationals or the country is not party to international treaties on extradition. Consequently, the international community has had to adopt many international conventions which binds states to either prosecute or extradite so that these criminals will be punished .